Seroprevalence of hepatitis E in HIV infected patients in Greece. Issue 9 (12th May 2015) - Politou, Marianna; Boti, Sofia; Androutsakos, Theodoros; Valsami, Serena; Pittaras, Theodoros; Kapsimali, Violetta
<x xml:space="preserve">Abstract</x> HEV infection is an emerging public health problem worldwide Data concerning HEV infection in HIV+ patients in Greece is scare. The aim of the study was to determine HEV seroprevalence in patients with HIV infection in Greece. We studied 243 HIV(+) patients 214 men (88%) and 29 women (12%) with a median age of 45 years (range 19–83) who attended the HIV unit of Pathophysiology Department of Laikon General Hospital in Athens for the presence of anti‐HEV IgG antibodies with (EIA) (EIA HEV IgG, Adaltis, Rome, Italy Eighteen/243 patients (7.3%) were positive for HEV IgG antibodies, a seroprevalence that was not different from that described for the blood donors group from Greece There was no difference of the presence of HbsAg, hepatitis C and hepatitis A between the HEV(+) and HEV(−) patients. There was no statistically significant difference between the HEV(+) and HEV(−) group in terms of HIV acquisition, sexual orientation, median duration of HIV infection, ART treatment, or duration of ART. Only the median age of HEV(+) was 52years (35–78) while that of HEV(−) was 44years (19–83)(P = 0.03). Only 2/18(11.1%) HEV(+) HIV(+) patients had abnormal ALT and AST values. The seroprevalence of hepatitis E in HIV(+) patients in Greece seems to be the same with that of the general population thus implying that HIV infection is not a risk factor for HEV infection and only age shows a positive correlation with seropositivity. J. Med. Virol. 87:1517–1520, 2015. © 2015 Wiley Periodicals, Inc.